2015
DOI: 10.1074/jbc.r115.658823
|View full text |Cite
|
Sign up to set email alerts
|

1-Deoxysphingolipids Encountered Exogenously and Made de Novo: Dangerous Mysteries inside an Enigma

Abstract: The traditional backbones of mammalian sphingolipids are 2-amino, 1,3-diols made by serine palmitoyltransferase (SPT). Many organisms additionally produce non-traditional, cytotoxic 1-deoxysphingoid bases and, surprisingly, mammalian SPT biosynthesizes some of them, too (e.g. 1-deoxysphinganine from l-alanine). These are rapidly N-acylated to 1-deoxy-“ceramides” with very uncommon biophysical properties. The functions of 1-deoxysphingolipids are not known, but they are certainly dangerous as contributors to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 97 publications
(131 reference statements)
0
93
0
Order By: Relevance
“…Because of their only recent identification in humans, very little is known about effects and functions of deoxySLs (49). In this study, we addressed some fundamental questions about the cellular metabolism and localization of de-oxySLs, potentially leading to novel insights about their pathomechanism in diseases like diabetic neuropathy and HSAN1.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their only recent identification in humans, very little is known about effects and functions of deoxySLs (49). In this study, we addressed some fundamental questions about the cellular metabolism and localization of de-oxySLs, potentially leading to novel insights about their pathomechanism in diseases like diabetic neuropathy and HSAN1.…”
Section: Discussionmentioning
confidence: 99%
“…The conjugation of L-alanine forms the DSL deoxy-sphinganine; when glycine is used in the reaction, deoxy-methylsphinganine is formed (Rotthier et al 2010). Because both of these sphingolipid metabolites do not contain the hydroxyl group normally located at C-1 in the sphinganine molecule formed when L-serine is used in the reaction catalyzed by SPT, these modified sphingolipids cannot be further metabolized to the more complex sphingolipids nor can they be degraded via the normal physiologic sphingolipid catabolic pathways to form 1-phosphate derivatives (Duan and Merrill 2015). Analysis of DSL in plasma revealed that DSL are present at low levels in plasma from normal, healthy individuals, primarily in very low density and low-density lipoproteins (Bertea et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The configuration of some asymmetric carbons in SPLs were assigned based on the de novo SPL biosynthetic pathway reported in the reference (Supplementary Figure S3). As a fungi, possible SPLs synthesis process of Cordyceps may involve a de novo SPL biosynthetic pathway in all eukaryotic cells161718, metabolism of fungi phytosphingolipid1920, as well as biosynthetic pathway of non-traditional 1-deoxysphingoid bases2122. These publications reported common sphingolipids metabolism existing in all eukaryotic cells and special biosynthetic pathway of sphingolipids in fungi, which provided important evidence to describe the plausible biosynthetic pathway of sphingolipids in Cordyceps.…”
Section: Resultsmentioning
confidence: 79%